2012
DOI: 10.3109/02699052.2012.655362
|View full text |Cite
|
Sign up to set email alerts
|

Do traditional executive measures tell us anything about daily-life functioning after traumatic brain injury in Spanish-speaking individuals?

Abstract: The current findings suggest that traditional performance-based executive measures reveal some degree of ecological validity or real-world relevance, providing relevant information for predicting everyday competence after moderate-to-severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
3
25
3
1
Order By: Relevance
“…Although the associated effect size was somewhat small, about a third of a standard deviation, this stands in contrast to recent findings in a study that focused on persons with moderate-severe TBI, where no significant differences between self-and informant reports were found. 13 The confluence of these findings is consistent with our interpretation of the effect of neuroimaging findings, that is, patients with mild TBI may have a somewhat (inadvertently) deflated perception of their executive abilities. A contributing factor in this regard may be the phenomenon of diagnosis threat, referring to the possibility that simply having too much attention paid to a history of mild TBI and its possible sequelae may result in negative self-expectations.…”
Section: Informant Ratings Of Executive Functioning After Mild Tbisupporting
confidence: 84%
See 2 more Smart Citations
“…Although the associated effect size was somewhat small, about a third of a standard deviation, this stands in contrast to recent findings in a study that focused on persons with moderate-severe TBI, where no significant differences between self-and informant reports were found. 13 The confluence of these findings is consistent with our interpretation of the effect of neuroimaging findings, that is, patients with mild TBI may have a somewhat (inadvertently) deflated perception of their executive abilities. A contributing factor in this regard may be the phenomenon of diagnosis threat, referring to the possibility that simply having too much attention paid to a history of mild TBI and its possible sequelae may result in negative self-expectations.…”
Section: Informant Ratings Of Executive Functioning After Mild Tbisupporting
confidence: 84%
“…20 However, in a recent study of adults with moderate-severe TBI, no significant differences between self-and family-reported BRIEF-A ratings were found. 13 In contrast, Rabin and colleagues 7 found that patients with mild cognitive impairment were more likely than their informants to report clinically significant problems on the BRIEF-A. Therefore, the degree of agreement between self-and informant ratings on the BRIEF-A that is to be expected after mild TBI remains uncertain.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, only one study exists and this study found a significant association between informant-reported EF difficulties on the BRIEF-A and activity of daily living problems on the Patient Competency Rating Scale in moderate-to-severe traumatic brain injury (García-Molina et al, 2012). The paucity of work is surprising in light of evidence from the child literature that parent ratings on the BRIEF correlate with scores on measures of adaptive functioning (Gilotty, Kenworthy, Sirian, Black, & Wagner, 2002;Mangeot et al, 2002).…”
Section: Introductionmentioning
confidence: 70%
“…Specifically, higher scores on the Digit Span subtest of the Wechsler Adult Intelligence Scale-Third Edition, a measure of auditory attention/working memory, were associated with lower self-reported difficulties on the BRIEF-A Metacognitive Index and Global Executive Composite. A third study found several significant associations between the BRIEF-A and objective-based measures of EF in adults with moderate-to-severe traumatic brain injury (García-Molina, Tormos, Bernabeu, Junqué, & Roig-Rovira, 2012). Specifically, poorer scores on the Trail Making Test-B, Stroop Color Word Interference Test, Controlled Oral Word Association Test, and Letter-Number Sequencing Test were associated with greater informant-reported difficulties on several BRIEF-A clinical scales.…”
Section: Introductionmentioning
confidence: 93%